Células estromais mesenquimais indiferenciadas alogênicas, ultrassom terapêutico ou laser no tratamento de feridas cutâneas de coelhos - Rosa, Maurício Borges da (2012)
The skin is the protection, thermoregulation, and control of water loss from the body. When there is continuity injury in this tissue, any kind of trauma can alter its functions. The healing process depends on factors such as location and size of the lesion, age and systemic conditions of the patient and the surgical technique used to repair it. Attempts to intervene in healing dates back to antiquity, when it was already recognized the importance of protecting the wounds to avoid complications in the process. Some resources are used as adjuvants in the healing process in order to obtain better results. For this experiment, we used 20 New Zealand White rabbits (Oryctolagus cuniculus). The animals were randomly divided into four groups of five animals each, in which we performed a skin wound 4cm ². In group A, animals received no treatment, group B was treated with transplantation of autologous mesenchymal stem cells, group C was treated with local application of therapeutic ultrasound, and group D laser was applied on site. The wounds were assessed at 7, 14 and 21 days postoperatively by measuring the area and biopsy. At the end of the study it was observed a statistical difference the group treated with cells in the healing process between groups.